2016
DOI: 10.1007/s00340-016-6355-6
|View full text |Cite
|
Sign up to set email alerts
|

Cantilever-enhanced photoacoustic detection of hydrogen sulfide (H2S) using NIR telecom laser sources near 1.6 µm

Abstract: concentrations as low as 500 pptv manifesting in the characteristic odor of rotten eggs can already be detected by the human olfactory sense, the total loss of olfactory sensation starts at 150-200 ppmv [3]. Because of the wide occurrence of H 2 S in industrial processes and its often negative impact on process stabilities and product quality, its concentration needs to be tightly monitored. Furthermore, safety considerations and legal concentration limits also necessitate the accurate determination of H 2 S l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…A detection limit of 9 ppb was achieved with an integration time of 10 s. If the microphone noise is higher than the acoustic noise caused by the environment, the sensitivity of the gas detection system based on PAS can be effectively improved by increasing the sensitivity of acoustic sensors. Therefore, various high-sensitivity acoustic sensors have been proposed in recent years, such as quartz tuning fork [9][10][11], fiber-optic acoustic sensor [12][13][14][15], and optical cantilever [16][17][18]. Wu et al developed a quartz-enhanced PAS (QEPAS) based NH 3 gas detection system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detection limit of 9 ppb was achieved with an integration time of 10 s. If the microphone noise is higher than the acoustic noise caused by the environment, the sensitivity of the gas detection system based on PAS can be effectively improved by increasing the sensitivity of acoustic sensors. Therefore, various high-sensitivity acoustic sensors have been proposed in recent years, such as quartz tuning fork [9][10][11], fiber-optic acoustic sensor [12][13][14][15], and optical cantilever [16][17][18]. Wu et al developed a quartz-enhanced PAS (QEPAS) based NH 3 gas detection system.…”
Section: Introductionmentioning
confidence: 99%
“…A distributed feedback (DFB) diode laser boosted by an EDFA combined with a quartz tuning fork was used for trace NH 3 detection. Experiments showed that the detection limit could reach 52 ppb [18]. Ma et al reported a sensitive QEPAS based NH 3 sensor [20].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a variety of online monitoring options for gaseous hydrogen sulfide, its reliable quantitative and selective determination still remains challenging in the field of chemical sensors [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In practice, concentrations ranging from sub-ppmv levels at low pressures to several per cents at atmospheric conditions need to be monitored. Despite a variety of online monitoring options for gaseous H 2 S, its reliable quantitative and selective determination still remains challenging in the field of chemical sensors [3][4][5].…”
mentioning
confidence: 99%
“…In practice, concentrations ranging from sub-ppmv levels at low pressures to several per cents at atmospheric conditions need to be monitored. Despite a variety of online monitoring options for gaseous H 2 S, its reliable quantitative and selective determination still remains challenging in the field of chemical sensors [3][4][5].In the field of laser spectroscopy, the constant improvement of quantum cascade lasers (QCLs) has led to their application as reliable sources of coherent light ranging from the mid-infrared (MIR) to the terahertz spectral region for sensitive detection of molecular species on their fundamental vibrational, respectively, rotational bands [6][7][8][9]. Due to their tailorable emission wavelength, high output power, compactness, narrow spectral linewidth, and wavelength tuneability, QCLs are optimal choices for spectroscopic applications.…”
mentioning
confidence: 99%